Reviewing the development, evidence base, and application of the revised dengue case classification - Horstick, Olaf (Pathogens and global health, 2013)
With the example of dengue, an evidence-based approach to prospectively develop a case classification is described, gathering evidence for identifying strength and weaknesses of the existing model, collecting new data describing the disease as it occurs globally, further developing a new model that can be applied in practice and field testing the newly developed model in comparison to the previous model. For each step in this process, the highest available level of evidence has been applied. This process has been initiated by the World Health Organization’s (WHO) Special Programme for Research and Training in Tropical Diseases (TDR) and WHO’s Department for Control of Neglected Tropical Diseases (NTD), developing the following for dengue. Since the early 1970s, dengue has been classified into dengue fever, dengue haemorrhagic fever grades I and II and dengue shock syndrome grades III and IV (DF/DHF/DSS). However, in recent years, a growing number of dengue clinicians have questioned the shortcomings of this scheme. The issues have revolved around the complexity of confirming DHF in clinical practice, misclassifying severe cases as DF, and the emphasis on haemorrhage rather than plasma leakage as the underlying problem in most severe dengue cases. Step 1: A systematic literature review highlighted the shortcomings of the DF/DHF/DSS scheme: (1) difficulties in applying the criteria for DHF/DSS; (2) the tourniquet test has a low sensitivity for distinguishing between DHF and DF; and (3) most DHF criteria had a large variability in frequency of occurrence. Step 2: An analysis of regional and national dengue guidelines and their application in the clinical practice showed a need to re-evaluate and standardize guidelines as the actual ones showed a large variation of definitions, an inconsistent application by medical staff, and a lack of diagnostic facilities necessary for the DHF diagnosis in frontline services. Step 3: A prospective cohort study in seven countries, confirmed the difficulties in applying the DF/DHF/DSS criteria even in tertiary care hospitals, that DF/DHF/DSS do not represent levels of disease severity and that a clear distinction between severe dengue (defined by plasma leakage and/or severe haemorrhage, and/or organ failure) and (non-severe) dengue can be made using highly sensitive and specific criteria. In contrast, the sub-grouping of (non-severe) dengue into two further severity levels was only possible with criteria that gave approximately 70% sensitivity and specificity. Step 4: Three regional expert consensus groups in the Americas and Asia concluded that ‘dengue is one disease entity with different clinical presentations and often with unpredictable clinical evolution and outcome’ and that, revising the results of Step 3, DF/DHF/DSS is not related to disease severity. Step 5: In a global expert consensus meeting at WHO in Geneva/Switzerland the evidence collected in Steps 1-4 was reviewed and a revised scheme was developed and accepted, distinguishing: dengue with or without warning signs and severe dengue; the further field testing and acquisition of further prospective evidence of the revised scheme was recommended. Step 6: In 18 countries, the usefulness and applicability of the revised classification compared to the DF/DHF/DSS scheme were tested showing clear results in favour of the revised classification. Step 7: Studies are under way on the predictive value of warning signs for severe dengue and on criteria for the clinical diagnosis of dengue which will complete the evidence foundation of the revised classification. The analysis has shown that the revised dengue case classification is better able to standardize clinical management, raise awareness about unnecessary interventions, match patient categories with specific treatment instructions, and make the key messages of patient management understandable for all health care staff dealing with dengue patients. Furthermore, the evidence-based approach to develop prospectively the dengue case classification could be a model approach for other disease classifications.
Published online: 12 Nov 2013
Gesehen am 05.09.2018